2011
DOI: 10.4317/medoral.17095
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a possible association between oral lichen planus and drug intake. A controlled study

Abstract: Objectives: To investigate whether daily systemic and/or topical medication contributes to the development of oral lichen planus (OLP) lesions. Study Design: The study involved 110 OLP patients and 76 control subjects, matched by age, race and sex. The analyzed data included medical records, drug intake and topical medication. Criteria for analysis of drug intake included: (1) ATC-code drug classification; (2) number of different drugs used daily in the categories of monopharmacy (1 drug), minor polypharmacy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 18 publications
6
21
3
3
Order By: Relevance
“…A very similar odd ratio estimates were found by Siponen et al [11] for the associacion of any thyroid diseases and OLP, particularly with hypothyroidism. Except in present study, a higher intake of thyroid medication among patients with OLP has also been found in three additional studies [24, 25,13]. Recent publication by Robledo-Sierra et al [13] suggested that it is hypothyroidism and not the drug that is associated with OLP.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A very similar odd ratio estimates were found by Siponen et al [11] for the associacion of any thyroid diseases and OLP, particularly with hypothyroidism. Except in present study, a higher intake of thyroid medication among patients with OLP has also been found in three additional studies [24, 25,13]. Recent publication by Robledo-Sierra et al [13] suggested that it is hypothyroidism and not the drug that is associated with OLP.…”
Section: Discussionsupporting
confidence: 67%
“…Eleven of them had histological confirmation of all cases with distinguish between OLP and OLL [1,11,23,25,[27][28][29][30][31][32][33] and five presented with control group [11,13,24,25,27]. It can be noticed clear difference in reported coexistence of thyroid gland pathosis and OLP between Northern and Central European countries (Finland [11], Czech Republic [28] and Croatia [34]) and Southern Mediterranean countries (Italy [1,26] and Turkey [29]).…”
Section: Discussionmentioning
confidence: 99%
“…Características demográficas do presente estudo mostraram que o LPO ocorreu predominantemente em indivíduos acima de 40 anos (média 50 anos) e do sexo feminino (proporção mulher/homem de 3.1:1), em concordância com o observado em estudos semelhantes (Eisen, 2002;Xue et al, 2005;Ingafou et al, 2006;Hirota et al, [2010]). Embora esta relação não foi verificada no presente estudo, a condição xerostômica 50 fora mais associada aos grupos de pacientes com lesões orais (LPO e não-LPO: 41%) do que no grupo de indivíduos sem lesões orais (controle-saudável: 25%).…”
Section: Discussionunclassified
“…Estudos relativos ao consumo de álcool e tabaco por portadores de LPO constataram que o número de pacientes LPO que possuem esses hábitos nocivos não é maior quando comparado com a população em geral (Gorsky et al, 1996;Silverman;Bahl, 1997;Mignona et al, 2001, Hirota et al, [2010). …”
Section: Mecanismo Etiopatogênicounclassified
See 1 more Smart Citation